Effects of Micro-topography Modification on Soil Moisture Dynamics in Cold and Arid Mining Areas of Southern Piedmont of Tianshan Mountain - Lu Yuanbo; Yan Cheng; Song Chunwu; Li Yajuan; Lai Chengyun; Zhu Jialong (Shuitu baochi tongbao)
[Objective] The effects of spatial and temporal dynamics of soil moisture on micro-topography modification (0—50 cm) were determined in order to provide a scientific basis and theoretical support for land reclamation and ecosystem reconstruction in cold and arid mining areas of the southern piedmont of Tianshan Mountain. [Methods] The study was conducted in the coal-mining area of Baicheng Runhua. Micro-topography changes to the overburden platform and slope of reclaimed mine land were evaluated. Soil moisture content was monitored from May to November 2022 for comparative experimental analysis. [Results] The soil moisture content of the platform storage ditch and the catchment slope transformation increased 37.03% and 25.85% respectively, and the relative enhancement effect was shown to be catchment slope > storage ditch. The water storage ditch and the catchment slope modification methods improved the temporal stability of soil moisture, and their relative effects were found to be water storage ditch > catchment slope. The soil moisture contents of the side slope reverse-slope terraces and the fish-scale pit transformation increased by 6.48% and 13.22%, respectively, and the relative enhancement effect was shown to be fish-scale pit> reverse-slope terrace. The fish-scale pit transformation method improved the temporal stability of soil moisture, and the reverse-slope terrace transformation method reduced the temporal stability of soil moisture. [Conclusion] Under the two topographical conditions of platform and side slope, the transformation of the catchment slope was more conducive to the ecological management of the damaged mine platform, and the transformation of the fish-scale pit was more conducive to the ecological management of the damaged mine slope.